Investigation of merging/reconnection heating during solenoid-free startup of plasmas in the MAST Spherical Tokamak. (3rd April 2017) - Tanabe, H.; Yamada, T.; Watanabe, T.; Gi, K.; Inomoto, M.; Imazawa, R.; Gryaznevich, M.; Scannell, R.; Conway, N.J.; Michael, C.; Crowley, B.; Fitzgerald, I.; et al.
Abstract: We present results of recent studies of merging/reconnection heating during central solenoid (CS)-free plasma startup in the Mega Amp Spherical Tokamak (MAST). During this process, ions are heated globally in the downstream region of an outflow jet, and electrons locally around the X -point produced by the magnetic field of two internal P3 coils and of two plasma rings formed around these coils, the final temperature being proportional to the reconnecting field energy. There is an effective confinement of the downstream thermal energy, due to a thick layer of reconnected flux. The characteristic structure is sustained for longer than an ion–electron energy relaxation time, and the energy exchange between ions and electrons contributes to the bulk electron heating in the downstream region. The peak electron temperature around the X -point increases with toroidal field, but the downstream electron and ion temperatures do not change.